Metrics to Measure Open Geospatial Data Quality. - Jingfeng Xia (Issues in Science and Technology Librarianship)
This paper explores measurement standards on the quality of open geospatial data with the purpose of optimizing data curation and enhancing information systems in support of scientific research and related activities. A set of dimensions for data quality measurement is proposed in order to develop appropriate metrics. [ABSTRACT FROM AUTHOR]